2014
DOI: 10.1016/j.aop.2014.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Is space-time symmetry a suitable generalization of parity-time symmetry?

Abstract: We discuss space-time symmetric Hamiltonian operators of the form H = H 0 +igH ′ , where H 0 is Hermitian and g real. H 0 is invariant under the unitary operations of a point group G while H ′ is invariant under transformation by elements of a subgroup G ′ of G. If G exhibits irreducible representations of dimension greater than unity, then it is possible that H has complex eigenvalues for sufficiently small nonzero values of g. In the particular case that H is parity-time symmetric then it appears to exhibit … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…the so-called space-time symmetry did not prove to be so robust in producing nonHermitian operators with real spectra [9][10][11][12].…”
mentioning
confidence: 99%
“…the so-called space-time symmetry did not prove to be so robust in producing nonHermitian operators with real spectra [9][10][11][12].…”
mentioning
confidence: 99%
“…In the multidimensional case H 0 and H may exhibit more complex symmetry that is conveniently described by means of group theory. In this way Fernández and Garcia [17,18] and Amore et al [19,20] found that some ST-symmetric Hamiltonians exhibit broken ST symmetry for all values of g. The main conjecture was that ST symmetry may be unbroken for some values of g provided that S is the only member of a class in the point group for H 0 [20]. This appeared to be the case when S = P .…”
Section: Introductionmentioning
confidence: 89%
“…The latter case may only take place when the spectrum of H is degenerate. In many cases it suffices to calculate the simplest, straightforward perturbation correction of first order E (1) [17][18][19][20].…”
Section: Most Of the Examples Studied So Far Are Of The Formmentioning
confidence: 99%
See 1 more Smart Citation
“…However, such treatments of symmetry look rather rudimentary when compared with the more rigorous approach carried out, for example, by Pullen and Edmonds [25,26]. Those enlightening papers motivated the application of point-group symmetry (PGS) to several multidimensional non-Hermitean anharmonic oscillators that led to most interesting conclusions [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%